Proposed new interior design of 3Run My One Stop Training Centre for 3Run My Parkour Community at Lot 2395, Seksyen 41, Jalan Sultan Ismail, Bandaraya Kuala Lumpur / Muhammad Juni Haikal Adnan - Adnan, Muhammad Juni Haikal (Faculty of Architecture, Planning and Surveying, 2011)
A final year student pursuing a diploma course in Interior Design is requisite to organize a final year project. All the design must be connected to the project that has been decided. Before making the design, major aspect must be considered to get the information. The research, case study, design schematic and the planning have to be done to make sure that client will give the good reaction to our design. Because of that, the organized work must been done perfectly starting from the design development until the end of the project. Proposed new interior design scheme for 3RUN MY Training Centre is one of the compensation to the client to establish their scope of extreme sports in Malaysia since this community already exists in Malaysia and getting well known by Malaysian. 3RUN MY also want to make a great platform for them to open people’s eyes to not misjudged about their activities. They also want to have a proper place for them to enjoy their activities with a better space not like before which they need to practice at randomly pick places. According to the objectives and the issues, a space planning must be suitable with the design concept and images. So, to realize the design into space is a difficult way because it has the procedures that must be followed. The planning has been produced and the ideas that wanted to be applied into the space must be linked to the concept and images. By that, the good design is produced with the concept, the images, into the design axis and followed by the development of ideas.